The coal trap : how West Virginia was left behind in the clean energy revolution - Van Nostrand, James M. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Between 2009 and 2019, West Virginian politicians aligned themselves with the interests of the coal industry to the substantial detriment of the citizens and economy of the state. Despite the undeniable low-carbon transformation that was occurring in the energy industry in the US during this period, state political leaders doubled down on coal. Rather than provide the leadership necessary to manage the transition of the state's economic drivers away from fossil fuels, they largely blamed the demise of the coal industry on the federal government. At every turn, the interests of the coal industry were placed above the economic and environmental health of West Virginians. James Van Nostrand tells the story of why West Virginia now faces overwhelming obstacles to competing in the economic marketplace of the twenty-first century. The book serves as a warning of how a fair energy transition can be derailed by political failure.
Introduction : "the lost decade" -- The rise of environmental regulations under Obama's EPA -- The Shale gas revolution -- The rise of renewable energy -- The Ds of today's electric utility industry : decarbonization and decentralization -- From "friends of coal" to the "war on coal" : how West Virginia went from blue to red -- "Leadership" from Washington, DC : the Congressional delegation that could have but didn't -- "Manchin in the middle" -- The failure of the public service commission to serve the public -- The role of the legislature in West Virginia's failed energy policies -- Bailing out the coal industry on the back of West Virginia electric ratepayers -- Coal operators get rich and West Virginia gets to clean up the mess -- What the future could hold if the leaders choose to lead.
Title from publisher's bibliographic system (viewed on 22 Jul 2022).
Keywords: Coal trade -- West Virginia -- History -- 21st century; Coal mines and mining -- West Virginia -- History -- 21st century; Energy policy -- Environmental aspects -- United States -- History -- 21st century